The Roots of Amerta Movement An Introduction to the Movement Improvisation of Suprapto Suryodarmo. - Lavelle, Lise (Triarchy Press, 2021)
Covering the early years of Javanese movement artist Prapto's teaching (1986-1997), this is a record of that period of his work.